Girl Reserves at Lowell School - Johnson, Charles Ellis, 1857-1926 (photographer):::Creator::::::::::::; Tucker, John O. (photographic studio):::Contributor::::::::::::
This photograph depicts an outdoors group portrait of the Girl Reserves at Lowell School in San Jose, California taken in 1925. Most of the girls are in their Girl Reserves uniforms. There is a woman dressed in dark clothes amidst the girls.